Preparation of Layered Double Hydroxide-Polyoxometalate Based Composite - Yulizah Hanifah; Amri Amri (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2023)
Material NiAl-K3[α-PW12O40], NiAl-K4[α-SiW12O40], ZnAl-K4[α-SiW12O40] and ZnAl-K3[α-PW12O40] were created. FTIR, XRD and SEM were used to characterize the substance. The findings of the successfully completed synthesis showed that peak diffraction angle for NiAl-LDH were at 11.58°, 23.18°, 35.01°, 39.41°, 46.70°, 60.94°, and 62.26° and diffraction at 10.29°, 20.07°, 34.02°, and 60.16° for ZnAl-LDH. The composite material LDH-polyoxometalate NiAl-PW12O40 that was at angles 10.76°, 26.59°, 30.8° and 63.1° and 8.61°, 25.27°, 33.8°, 66.34° for ZnAl-plyoxometalate. The typical polyoxometalate band on the composite material’s FTIR spectrum proved tha intecalation of the substance. SEM examination revealed the aggregat for nearly all intercalated and synthesized materials.